Effect of increased temperature and drought associated to climate change on productivity of nodulated alfalfa - Aranjuelo I.; Irigoyen J.J.; Sánchez-Díaz M. (Quality in lucerne and medics for animal production, 2001)
The aim of our study was to investigate the effect of a 3 degrees C increase in air temperature and low water availability upon dry matter production. Two month-old plants inoculated with Rhizobium meliloti were grown in growth chambers at 25 degrees C well (W25) or partially irrigated degrees (D25) and at 28 degrees C well (W28) or partially irrigated (D28). Drought and elevated temperature reduced the plant dry matter (DM) production and leaf area, especially when they were applied simultaneously. Lower leaf area and net photosynthetic rates induced by elevated temperatures explained the reduction in DM production at leaf level. Most of the photosynthetic limitations were due to lower Rubisco activity. Also, lower nodule mass and activity reduced the nitrogen available to the plants subjected to elevated temperature. Results are discussed in connection to the effect of a potential temperature increase associated to elevated CO2 in atmosphere.
14. Réunion Eucarpia du Groupe Medicago spp., 2001/09/12-15, Zaragoza and Lleida (Spain)